The boost chopper controlled by an 8-bit microcontroller (PIC16F873) / Yahya Yaakob - Yaakob, Yahya (2006)
This thesis presents a report on a prototype of the closed loop boost chopper controlled by an 8-bit microcontroller. In order to demonstrate the functionality of the converter, the boost chopper operating in the steady state condition has been designed and tested using closed loop and PIC16F873 microcontrollers. System modeling, main design procedures, as well as some hardware and software implementation issues are discussed. The objective of a closed loop boost chopper is to produce a stabilized variable high voltage output. The DC output voltage of the chopper is controlled by reference signals. Experimental and simulation results that demonstrate the performance of the converter are presented.